Representación de la violencia doméstica en la prensa española - Aran Ramspott, Sonia; Medina Bravo, Pilar (Estudios sobre el Mensaje Periodístico, 2006)
It analyses the visibility and social awareness process about domestic violence that we are all noticing in our surroundings in the latest years. With this target the representation of this phenomenon is reviewed through the news appeared in the Spanish press in a whole month (March – April 2005), and with the observation of the treatment given to the first domestic death of the year it takes shape.
Keywords: Domestic violence; Press; Spain